Managing Excessive Gum Display Caused By Hyperactive Lip Movement with Coronally Placed Vestibulum - Michael Christian Tjandrawinata; Vinanto Putera; Agung Krismariono; Irma Josefina Savitri (Jurnal Pengabdian Ilmu Kesehatan, 2026)
An excessive gum display (EGD) refers to a smile that displays more than 2 mm of visible gingiva. Among dental patients, it is a prevalent aesthetic issue. It influences both psychological and aesthetic status since it typically lowers self-confidence. EGD is considered unaesthetic when smiling, thus many patients seek treatment to manage this condition. The etiology of EGD varies, with hypermobile upper lip (HUL) as the most predominant. HUL is defined as more than 8 mm of upper lip movement from rest to maximum smile. This article will discuss about the management of EGD caused by HUL, treated with coronally placed vestibulum. Case: A 28-year-old male patient came with a complaint of disproportionate gingival display. The patient felt that his gums were exposed too much when smiling. The patient was not confident with the condition. On maximum smile, 6 mm of gingiva was displayed due to hypermobile upper lip. The diagnose of excessive gum display was established. The treatment was coronally placed vestibulum, which done by relocating the attachment between the mucosa and the attached gingiva closer to the coronal. Follow-up results after 3 months showed a noticeable decrease in excessive gingival display. Discussion: Coronally placed vestibulum is performed on cases of EGD with the etiology of HUL. Through this procedure, the vestibule's limiting muscular pull is narrowed, reducing gingival display when smiling. Conclusion: Coronally placed vestibulum is a less-invasive treatment of choice for EGD caused by HUL.